(untitled) (Fiep Bulletin - online, 2013)
This study was conducted with one patient during the post-operative period of valve substitution with the objective to analyse the applicability of the Peplau nursing theory in practice. The referential was Peplau´s theory of nursing . Taxonomy of the North American Diagnosis Association (NANDA) was utilized to describe the patient´s reponse to his health situation. Five encounters were held with the patient during which the interview and observation techniques were used for data collection. Five nursing diagnoses were identified and nursing actions were implemented for the resolution of the identified problems. It is concluded that the appliction of the theory is possible, and that it has benefits and difficulties that need to be considered at its implementation.